Katalog favne hroščev votlin iz okolice Škofje Loke, Železnikov, Gorenje vasi in Žirov v zbirki CBKS. - Kofler, Bojan (Acta entomologica slovenica (Ljubljana), 2023)
The catalogue is a result of many years lasting research in 72 caves, abysses, schafts and mines. It was found 94 species and subspecies altogether. They belongs to eleven families: Agyrtidae, Carabidae, Cryptophagidae, Curculionidae, Latridiidae, Leiodidae, Nitidulidae, Pselaphidae, Rhizophagidae, Scydmaenidae, and Staphylinidae. Some of species and subspecies were new for the science at the time of the discovery.
Keywords: beetles; biodiversity; biodiverziteta; Biološka raznovrstnost; cavities; favna hroščev; Hrošči; Katalogi; Slovenia; Slovenija; votline